Macroscopic fiber orientation model evaluation for concentrated short fiber reinforced polymers in comparison to experimental data - Kugler, Susanne; Lambert, Gregory M.; Cruz, Camilo; Kech, Armin; Osswald, Tim A.; Baird, Donald G. (Polymer Composites, 2020)
Advanced macroscopic fiber orientation models depend on a variety of phenomenological parameters. The aim of this work is to identify a fiber orientation model for concentrated short fiber reinforced polymers, which depends on a minimum number of parameters. A sliding plate experiment with repeatable initial conditions and a couette experiment, to cover high strains, are used to define an experimental validation curve. The major fiber orientation models (Folgar and Tucker, nematic, reduced strain closure [RSC], anisotropic rotary diffusion, ARD-RSC) are fitted to the validation curve. Since a slow evolution can be observed, the RSC model is necessary to fit the measured fiber orientation evolution. The dependency of the RSC model on the initial fiber orientation state and the influence of closure approximations are evaluated. Two validation cases show that the obtained parameters give good results in shear dominant parts, but are not able to predict fiber orientation in other flow regimes accurately.
CRIS-Team Scopus Importer:2020-03-27
Keywords: fibers; modeling; orientation; thermoplastics